2016
DOI: 10.1002/adma.201601101
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearable Organic Nanocarriers for Bioimaging and Drug Delivery

Abstract: Graphical Abstract Renally cleared zwitterionic nanocarriers (H-Dots) are composed of ε-polylysine backbone for charge variations, near-infrared fluorophores for bioimaging, and β-cyclodextrins for potential drug delivery. H-Dots show ideal systemic circulation and rapid distribution and excrete from normal tissue/organ via renal excretion after complete targeting to the tumor site without nonspecific uptake by the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 33 publications
6
116
0
Order By: Relevance
“…[1][2][3][4][5] These nanoparticles are commonly injected intravenously, and during cargo delivery, they encounter various biological barriers in vivo, including blood circulation, tumor tissue penetration, cell internalization, and intracellular trafficking. [1][2][3][4][5] These nanoparticles are commonly injected intravenously, and during cargo delivery, they encounter various biological barriers in vivo, including blood circulation, tumor tissue penetration, cell internalization, and intracellular trafficking.…”
Section: Doi: 101002/adma201605357mentioning
confidence: 99%
“…[1][2][3][4][5] These nanoparticles are commonly injected intravenously, and during cargo delivery, they encounter various biological barriers in vivo, including blood circulation, tumor tissue penetration, cell internalization, and intracellular trafficking. [1][2][3][4][5] These nanoparticles are commonly injected intravenously, and during cargo delivery, they encounter various biological barriers in vivo, including blood circulation, tumor tissue penetration, cell internalization, and intracellular trafficking.…”
Section: Doi: 101002/adma201605357mentioning
confidence: 99%
“…For these reasons, the “Choi Criteria” should be the first and foremost important design considerations for clinically applicable NPs (reviewed in [8]): First, the components of NPs need to be selected from among nontoxic molecules and/or biodegradable components. Natural materials or FDA-approved molecules are good candidates, and organic materials are relatively advantageous over inorganic ones in this context [18]. Second, the surface charge of the NPs should be considered to minimize cellular interactions with normal tissue and thereby avoid nonspecific uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Kang et al suggested that H-Dots would be ideal to target specific disease sites as unbound particles would be rapidly eliminated from background tissues to the bladder [18]. As shown in Fig.…”
Section: Light-responsive Nanomedicine For Biophotonic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] For this reason, Choi et al designed zwitterionic near-infrared fluorophores to conjugate with targeting ligands, which show ultralow serum binding, negligible nonspecific tissue background, and rapid elimination from the body through urinary excretion. [54,5962] …”
Section: Contrast Agents For Optical Imagingmentioning
confidence: 99%